THE DEVELOPMENT OF INTERACTIVE LEARNING MEDIA BASED ON PROBLEM BASED LEARNING IN TRIGONOMETRY CONTENT FOR GRADE X AT SMA MUHAMMADIYAH 2 SINGARAJA: PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS PROBLEM BASED LEARNING PADA KONTEN TRIGONOMETRI KELAS X DI SMA MUHAMMADIYAH 2 SINGARAJA - Tri Arendo Yogiswara; Agustini Ketut; I Nyoman Indhi Wiradika (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2026)
Indonesia faces challenges in preparing its society for the 21st century, emphasizing the need for educational reforms that foster independence, responsibility, creativity, and innovation among students. In high school mathematics, particularly in trigonometry, many students struggle, indicating a gap between teaching methods and student understanding. Research shows that interactive multimedia learning tools can enhance engagement and comprehension. A study at SMA Muhammadiyah 2 Singaraja suggested that integrating Problem-Based Learning (PBL) with interactive media could address these difficulties, making trigonometry more accessible and stimulating for learners.